2013
DOI: 10.3109/17435390.2013.809809
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary toxicity of pulmonary exposure to occupationally relevant zinc oxide nanoparticles

Abstract: Exposure to zinc oxide (ZnO) metal fumes is linked to adverse human health effects; however, the hazards of ZnO nanoparticles (ZnONPs) remain unclear. To determine pulmonary exposure to occupationally relevant ZnONPs cause cardiopulmonary injury, Sprague-Dawley rats were exposed to ZnONPs via intratracheal (IT) instillation and inhalation. The relationship between intrapulmonary zinc levels and pulmonary oxidative-inflammatory responses 72 h after ZnONP instillation was determined in bronchoalveolar lavage flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 34 publications
3
86
0
Order By: Relevance
“…[24][25][26] We have previously shown that a 14-day continuous exposure of rats to ZnONPs caused significant cardiopulmonary impairment observed after a 28-day follow-up period. 9 However, the mechanisms underlying the acute and subacute effects of ZnONP exposure may be different. Also, a previous study showed that there was 0.14% of 65 ZnONPs remaining in the lungs after 28 days post-IT exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[24][25][26] We have previously shown that a 14-day continuous exposure of rats to ZnONPs caused significant cardiopulmonary impairment observed after a 28-day follow-up period. 9 However, the mechanisms underlying the acute and subacute effects of ZnONP exposure may be different. Also, a previous study showed that there was 0.14% of 65 ZnONPs remaining in the lungs after 28 days post-IT exposure.…”
Section: Discussionmentioning
confidence: 99%
“…1 In a rat model, pulmonary impairment and degeneration as well as necrosis of the myocardium were detected after 30 days of repeated exposure to ZnONPs. 9 Time-dependent responses, including mitochondrial dysfunction and oxidative stress, were observed in rat alveolar epithelial cell monolayers. 10 Together, these results imply that the health effects of ZnONP exposure may depend on the time following exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the simulation of 65 Zn(NO) 3 was well fitted with the experimental data. Therefore, it is likely that 65 ZnO NPs gradually decompose into zinc ion after 7 days.…”
Section: Particle Size-dependent Physicochemical Parametersmentioning
confidence: 99%
“…1 The biodistribution of NPs might markedly influence their biological effects in vivo, such as in inflammatory and oxidative responses related to cardiopulmonary toxicity. 2,3 Zinc oxide nanoparticles (ZnO NPs) are commonly used in sunscreens in particle sizes ranging from 70 nm to 100 nm because of strong ultraviolet absorptive properties. ZnO NPs also have potential application in the delivery of therapeutic agents for tumors and autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%